2022
DOI: 10.1111/ppc.13040
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between self‐transcendence and depressive symptoms, self‐esteem, and locus of control in individuals diagnosed with substance addiction

Abstract: Aims: This study examined the relationships between self-transcendence and depressive symptoms, self-esteem, and locus of control in persons with substance abuse disorder (SUDs).Methods: This descriptive-relational study examined 115 participants who had been diagnosed with SUD.Results: High self-transcendence scores were positively associated with lower levels of depressive symptoms, higher levels of self-esteem, and internal locus of control.Practice implications: Mental health nurses are effective at findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Several studies indicate that low self-esteem is frequently observed in patients with SUD. However, in contrast to this perspective, other studies that have examined the relationship between SUD and self-esteem have found high levels of self-esteem [37].…”
Section: Personality Factors and Addictionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies indicate that low self-esteem is frequently observed in patients with SUD. However, in contrast to this perspective, other studies that have examined the relationship between SUD and self-esteem have found high levels of self-esteem [37].…”
Section: Personality Factors and Addictionmentioning
confidence: 81%
“…Temperament and personality traits (e.g., disinhibition, self-control) contributing to addiction development and persistence. [31,32,37] Anxiety and Addiction…”
Section: Personality Factors and Addictionmentioning
confidence: 99%
“…Across many populations, individuals with high self-transcendence scores tend to have better mental health and well being [7][8][9][10][11] , presenting lower levels of depressive symptoms 12 , and higher levels of self-esteem and internal locus of control 13,14 . These relationships are consistent across many studies, according to a recent meta analysis 15 .…”
Section: Introductionmentioning
confidence: 99%